Progress in Research on Bacteriophage Receptor-Binding Proteins and Host Range Extension - LI Fan, YU Zhenxing, ZHANG Ming, LIN Hong, LI Xuepeng, LI Jianrong, ZHANG Defu (Shipin Kexue, 2023)
Phages are one of the most diverse and widely distributed organisms on the earth today, and have great advantages in eliminating bacteria, especially multi-drug resistant bacteria that are widespread at present. At present, a variety of bacteriophage products have been well applied in the fields of breeding for food raw materials, farmed animals, foodborne pathogenic bacteria detection, and instant food sterilization. However, the narrow host range and complex interaction mechanism between bacteriophage and host bacteria greatly limit their development as new bacteriostatic agents. The specific binding between bacteriophages and host bacteria depends on the receptor binding proteins on the surface of bacteriophages. Studying the structure, function and mechanism of action of various bacteriophage receptor binding proteins will help in understanding the interaction process between bacteriophage and bacteria. On this basis, phage receptor binding protein modification by genetic engineering and induced culture methods to obtain high-quality broad-spectrum phages has become an important content of phage research. This paper summarizes the current research on different structures of phage receptor binding proteins and various host spectrum expansion schemes in an effort to provide theoretical support for the development and application of bacteriophages in the food industry.